Simbol dan citra Bangsawan Jawa pada Pendopo Dalem Wuryaningratan - Agus Dody Purnomo; Febry Maharlika; Wahyu Dwi Utami (ARTEKS : Jurnal Teknik Arsitektur, 2023)
For Javanese people, a house serves as both a shelter and a symbol. a representation of one's value, dignity, and perfection as a human being, especially for men. According to Javanese philosophy, a man is considered ideal if he already possesses a wisma, wanodya, turangga, curiga, and kukila. The house can serve as both a symbol and a window into the personality of those who live there. The pendopo serves as a gathering place and performs various tasks while displaying the emblem and persona of the owner. The pendopo performs several roles that reflect social standing and the owner's image in addition to acting as a collaborative or public place. The research aims to examine the Dalem Wuryaningratan in Surakarta. The focus of the study is on the application of the symbol and image of the owner in the pendopo. The research method uses a qualitative approach that produces descriptive data through observing objects, conducting interviews, and reviewing documents. Dalem Wuryaningratan is a well-preserved heritage building in Surakarta. The building is a legacy of KPH Wuryaningrat, the original owner. Meanwhile, the new owner, Haji Santosa Doellah, is a batik entrepreneur in Surakarta. The building is now called the House of Danar Hadi, and it is located in the area of the Danar Hadi batik museum. The building is a mix of Javanese and European (Indische style). Although it is no longer a residential building, the image of Javanese nobility is still maintained to preserve the structure. In particular, the appearance of the pendopo reflects the status symbol and embodiment of Javanese nobility.